Determinants of Inflation in Iran and Policies to Curb It - Ture, H. Elif (IMF Working Papers; Working Paper, 2022)
High and volatile inflation has been an endemic economic and social issue in Iran that has contributed to rising poverty and social tensions. For policymakers to effectively address the inflation problem, it is critical to understand its causes. This paper seeks to contribute to this endeavor by applying a vector error-correction model to study the short- and long-term determinants of inflation in Iran over the past two decades and identify policy options to curb it. Using quarterly data spanning 2004-2021, it finds that money growth drives inflation only in the long term, while currency depreciation, fiscal deficits, and sanctions (proxied by oil exports) drive inflation both in the short- and the long term. In the absence of a removal of US trade and financial sanctions that could significantly boost the rial, budget deficits will have to be adjusted to contain inflation, albeit gradually to avoid hindering the recovery. Over the medium term, strengthening the inflation targeting framework could help improve monetary transmission and contain inflation durably.